Pengaruh CSR dan EPS terhadap Harga Saham pada Perusahaan yang Terdaftar di Jakarta Islamic Index - Silmi, Syaifa Scholastika; Sari, Widya (Ma'soem University, 2025)
This study aims to determine the effect of Corporate Social Responsibility and Earning Per Share on stock prices in companies listed on the Jakarta Islamic Index (JII) for the period 2020-2024. This research uses quantitative methods with an associative approach, using secondary data obtained from the company's annual report. The sampling technique used purposive sampling, with a population of all issuers listed on the JII during the 2020-2024 period which was 59 issuers and a sample of 12 issuers selected according to the criteria that have been set. The results showed that partially neither Corporate Social Responsibility nor Earning Per Share had any effect on stock prices. However, simultaneously Corporate Social Responsibility and Earning Per Share have an effect on stock prices of companies listed on the JII for the period 2020-2024.